2018
DOI: 10.1038/s41419-018-0815-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of DDHD2, whose mutation causes spastic paraplegia, promotes reactive oxygen species generation and apoptosis

Abstract: DDHD2/KIAA0725p is a mammalian intracellular phospholipase A1 that exhibits phospholipase and lipase activities. Mutation of the DDHD2 gene causes hereditary spastic paraplegia (SPG54), an inherited neurological disorder characterized by lower limb spasticity and weakness. Although previous studies demonstrated lipid droplet accumulation in the brains of SPG54 patients and DDHD2 knockout mice, the cause of SPG54 remains elusive. Here, we show that ablation of DDHD2 in mice induces age-dependent apoptosis of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Loss of DDHD2 in mouse embryonic fibroblasts increased mitochondrial membrane potential and reduced ATP production and O 2 consumption. These mitochondrial dysfunction were associated with production of reactive oxygen species (Maruyama et al, 2018). Similar to loss of DDHD2, lymphoblasts of SPG28 patients devoid of DDHD1 also presented higher ROS production and lower ATP production compared to control cells (Tesson et al, 2012).…”
Section: Mitochondria Dysfunctionmentioning
confidence: 86%
See 2 more Smart Citations
“…Loss of DDHD2 in mouse embryonic fibroblasts increased mitochondrial membrane potential and reduced ATP production and O 2 consumption. These mitochondrial dysfunction were associated with production of reactive oxygen species (Maruyama et al, 2018). Similar to loss of DDHD2, lymphoblasts of SPG28 patients devoid of DDHD1 also presented higher ROS production and lower ATP production compared to control cells (Tesson et al, 2012).…”
Section: Mitochondria Dysfunctionmentioning
confidence: 86%
“…Excessive fusion observed in the absence of DDHD1 or DDHD2 could explain the accumulation of dysfunctional mitochondria and thus impaired ATP production, which could contribute to neurodegeneration. Importantly, the alteration of mitochondrial function in DDHD2 knockout fibroblasts was not associated with the accumulation of LD or increased levels of TAG, but it was associated with decreased levels of cardiolipin, a mitochondriaspecific lipid class (Maruyama et al, 2018). Cardiolipin can regulate the fusion of mitochondria and the formation of mitochondrial respiratory supercomplexes (Mileykovskaya and Dowhan, 2014;Kameoka et al, 2018).…”
Section: Mitochondria Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to DDHD1, DDHD2 KO mice exhibited a typical HSP phenotype, including age-dependent apoptosis of motor neurons in the spinal cord ( Maruyama et al, 2018 ). DDHD2 depletion was found to not inhibit neurite outgrowth or enhance the recycling pathway ( Supplementary Figures S2 , S8 ).…”
Section: Discussionmentioning
confidence: 99%
“…DDHD2 is also a causative gene for HSP (SPG54), and the patients exhibit a lipid peak in the brain detectable on magnetic resonance spectroscopy ( Schuurs-Hoeijmakers et al, 2012 ; Doi et al, 2014 ). The HSP phenotype and neutral lipid accumulation of SPG54 could be reproduced in DDHD2 KO mice ( Inloes et al, 2014 ; Maruyama et al, 2018 ), and DDHD2 was found to possess triacylglycerol lipase activity ( Inloes et al, 2014 ) and DAG lipase activity ( Araki et al, 2016 ; Aso et al, 2016 ). Although it has been suggested that neutral lipid accumulation in the brain is a cause of SPG54 ( Inloes et al, 2014 ), our recent study involving DDHD2 KO mice and cells suggested that reactive oxygen species (ROS) production in mitochondria in motor neurons also likely contributes to cell apoptosis and the onset of SPG54 ( Maruyama et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%